Proton‐Driven Transformable 1O2‐Nanotrap for Dark and Hypoxia Tolerant Photodynamic Therapy. Issue 17 (18th April 2022) - Chen, Dapeng; Dai, Hanming; Wang, Weili; Cai, Yu; Mou, Xiaozhou; Zou, Jianhua; Shao, Jinjun; Mao, Zhengwei; Zhong, Liping; Dong, Xiaochen; Zhao, Yongxiang
Abstract: Despite the clinical potential, photodynamic therapy (PDT) relying on singlet oxygen ( 1 O2 ) generation is severely limited by tumor hypoxia and endosomal entrapment. Herein, a proton‐driven transformable 1 O2 ‐nanotrap (ANBDP NPs) with endosomal escape capability is presented to improve hypoxic tumor PDT. In the acidic endosomal environment, the protonated 1 O2 ‐nanotrap ruptures endosomal membranes via a "proton‐sponge" like effect and undergoes a drastic morphology‐and‐size change from nanocubes (≈94.1 nm in length) to nanospheres (≈12.3 nm in diameter). Simultaneously, anthracenyl boron dipyrromethene‐derived photosensitizer (ANBDP) in nanospheres transforms to its protonated form (ANBDPH) and switches off its charge‐transfer state to achieve amplified 1 O2 photogeneration capability. Upon 730 nm photoirradiation, ANBDPH prominently produces 1 O2 and traps generated‐ 1 O2 in the anthracene group to form endoperoxide (ANOBDPH). Benefitting from the hypoxia‐tolerant 1 O2 ‐release property of ANOBDPH in the dark, the 1 O2 ‐nanotrap brings about sustained therapeutic effect without further continuous irradiation, thereby achieving remarkable antitumor performance. Abstract : A 1 O2 ‐nanotrap is prepared to combat hypoxic tumors. In proton‐rich endosomal environment, the 1 O2 ‐nanotrap can escape from endosomal entrapment by "proton‐sponge"‐like effect. Simultaneously, the 1 O2 ‐nanotrap undergo morphology‐and‐size transformation from nano‐cubes to nano‐spheres, allowing amplified PDT efficacy. Harnessing the reversible 1 O2 capture‐and‐release property, the 1 O2 ‐nanotrap bring sustained therapeutic effect without further continuous irradiation, which significantly enhance the antitumor efficacy.